Deteksi Anemia, Penyuluhan, Suplementasi Zat Besi Pada Ibu Hamil Di Desa Nagrak Dan Ciangsana, Bogor - Atut Cicih Mayasari; Rully Ayu Nirmalasari HP; Tiara Melati (CV. Multi Kreasi Media, 2023)
Indonesian anemic proportions in pregnant women were 48,9% in 2018 report from Statistic Registration of Republic of Indonesia. About 50% of anemia is caused by iron deficiency. This poses a severe public health problem in Indonesia since anemia in pregnancy contributes to 16 – 40% maternal deaths. It also causes morbidity during gestation, delivery, post and perinatal not only to the mother but also the baby. A cross-sectional study was conducted by investigating the level of hemoglobin in pregnant women at the Center of Science Technology and Community Development Nagrak. Other parameters measured include middle upper arm circumference (MUAC), body mass index (BMI, using categories from WHO Asia Pacific). Descriptive analysis and t-test was conducted using Microsoft Excel 2022. At the time of the study, 24 pregnant women participated. Twelve women were found anemic (50%, CI 95% 9,7 – 11,2). The mean level of hemoglobin amongst the anemic population were 9,14 (CI 95% 8,3 – 10). The study also found 13% of the population were underweight, and 17% had MUAC of less than 23,5 cm. This study finds 17% of anemic women were underweight (p value 0,000). Total of 25% of anemic women had MUAC of less than 23,5 cm (p value 0,000). Anemia in pregnancy is prevalent in women at the Center of Science Technology and Community Development Nagrak. Other associating parameters include BMI and MUAC. Thus, iterating the importance of routine education and close support for iron supplementation within the community.